Lonicerae flos and turmeric extracts alleviate necrotic enteritis in broilers by modulating gut-liver health and microbiota - Xingbo Liu; Yunru Ji; Huiyuan Lv; Zhong Wang; Zengpeng Lv; Yuming Guo; Wei Nie (Journal of Animal Science and Biotechnology)
Abstract Background Necrotic enteritis (NE) can cause intestinal barrier dysfunction in broilers, leading to secondary liver injury (SLI). In this process, the gut-liver axis plays a crucial role. Lonicerae flos and turmeric extracts (LTE), containing chlorogenic acid and curcumin, have been reported to possess anti-inflammatory, and antioxidant properties. Based on these potential biological benefits, this study aims to investigate the reparative effects of LTE on the intestinal barrier dysfunction in NE-infected broilers and assess its therapeutic efficacy in alleviating SLI. By elucidating the regulatory mechanisms of LTE on gut-liver axis health, this research provides new insights into the prevention and treatment of NE in broilers. Results LTE improved body weight and average daily gain while reducing intestinal lesion scores, coccidia oocysts, and Clostridium perfringens counts in NE broilers (P < 0.05). LTE enhanced intestinal morphology and up-regulated the expression of tight junction protein genes (CLDN1, TJP1) and MUC2, suppressed pro-inflammatory cytokine and myeloperoxidase (MPO) levels, and minimized endotoxin (ET) accumulation in NE broilers (P < 0.05). Furthermore, LTE alleviated oxidative stress in ileal cells and protected mitochondrial structure and function in NE broilers. NE infection induced intestinal permeability in broilers, leading to increased serum pro-inflammatory cytokines and intestinal-derived endotoxin levels, which caused liver damage. LTE significantly reduced liver pathologic damage, pro-inflammatory cytokine levels, aspartate transaminase, alanine aminotransferase, and ROS levels in NE broilers (P < 0.05). Additionally, 16S rRNA sequencing revealed that NE significantly increased the relative abundance of Barnesiella and decreased the relative abundance of Bacteroidota, Desulfobacterota and Bacteroides in the cecum of broilers. LTE enhanced intestinal microbiota diversity and reduced the segregation of intestinal microbiota induced by NE infection. Conclusions In summary, LTE can alleviate NE and SLI by modulating the microbiota, inhibiting inflammation and oxidative stress, and ameliorating mitochondrial dysfunction, thereby enhancing gut-liver axis health and growth performance.